Alternative pathways for the development of lymphoid structures in humans - Berteloot, Laureline (Proc Natl Acad Sci U S A, 2021)
Lymphoid tissue inducer (LTi) cells are critical for inducing the differentiation of most secondary lymphoid organs (SLOs) in mice. In humans, JAK3 and γc deficiencies result in severe combined immunodeficiency (SCIDs) characterized by an absence of T cells, natural killer cells, innate lymphoid cells (ILCs), and presumably LTi cells. Some of these patients have undergone allogeneic stem cell transplantation (HSCT) in the absence of myeloablation, which leads to donor T cell engraftment, while other leukocyte subsets are of host origin. By using MRI to look for SLOs in nine of these patients 16 to 44 y after HSCT, we discovered that SLOs were exclusively found in the three areas of the abdomen that drain the intestinal tract. A postmortem examination of a child with γc-SCID who had died 3.5 mo after HSCT showed corticomedullary differentiation in the thymus, T cell zones in the spleen, and the appendix, but in neither lymph nodes nor Peyer patches. Tertiary lymphoid organs were observed in the lung. No RAR-related orphan receptor-positive LTi cells could be detected in the existing lymphoid structures. These results suggest that while LTi cells are required for the genesis of most SLOs in humans, SLO in the appendix and in gut-draining areas, as well as tertiary lymphoid organs, can be generated likely by LTi cell-independent mechanisms.